Histological evaluation of cellular response to a multifilament electrospun suture for tendon repair - Rashid, M; Dudhia, J; Dakin, SG; Snelling, S; Lach, A; De Godoy, R; Mouthuy, P-A; Smith, R; Morrey, M; Carr, AJ (Public Library of Science, 2020)
Background